The rotavirus causing acute gastroenteritis in children of under 5-year of age in Indonesia 1972-2018: a review - Abu Tholib Aman (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
The reason of this review is the absence of thorough information of rotavirusinfection that had been the major cause of severe diarrhea in children of under5-years of age in Indonesia, despite numerous publications elaborating rotavirusinfection in some geographic areas of Indonesia. A review was conductedtowards 52 published articles covering rotavirus research in Indonesia duringperiod of 1972-2018.A thirty three selected articles were match with reviewcriteria which comprises rotavirus positive rate, clinical features, and severityof rotavirus infection, as well as genotypes of the rotavirus. Rotavirus has beenknown as the major cause of severe diarrhea among children under 5 years ofage world wide including in Indonesia. The rotavirus positive rates were rangefrom 31.1 to 90.9%, which variably to different subject’s population, studycriteria and methods, and time. Rotavirus can cause severe diarrhea withmajority of infected children suffered from dehydration, vomiting, and fever.The first genotyping conducted in Indonesia in the early 1980s revealed thepredominant genotypes were G3 and G4, followed by G2, and small proportionof G1 and mixed genotypes. However the following decades G1 and G2 were onthe raise with G3 predominantly re-appeared on 2015. G9 was first identified in2004, and occasionally detected until 2015. The P genotyping revealed P[4], P[6],and P[8] were the common genotypes detected. Mixed and untyped genotypeswere also detected in various proportion. Rotavirus diarrhea is a vaccinationpreventable disease, after natural infection, the immune system will produceprotective antibodies that will protect from infection of both homotypic andheterotypic, however homotypic infection will protect stronger. Therefore thisreview recommends continuous rotavirus genotypes surveillance in Indonesia.